The Relation Between Position and Chemical Composition of Bis‐Indole Substituents Determines Their Interactions with G‐Quadruplex DNA. Issue 43 (3rd July 2020) - Prasad, Bagineni; Das, Rabindra Nath; Jamroskovic, Jan; Kumar, Rajendra; Hedenström, Mattias; Sabouri, Nasim; Chorell, Erik
Abstract: G‐quadruplex (G4) DNA structures are linked to fundamental biological processes and human diseases, which has triggered the development of compounds that affect these DNA structures. However, more knowledge is needed about how small molecules interact with G4 DNA structures. This study describes the development of a new class of bis‐indoles (3, 3‐diindolyl‐methyl derivatives) and detailed studies of how they interact with G4 DNA using orthogonal assays, biophysical techniques, and computational studies. This revealed compounds that strongly bind and stabilize G4 DNA structures, and detailed binding interactions which for example, show that charge variance can play a key role in G4 DNA binding. Furthermore, the structure–activity relationships generated opened the possibilities to replace or introduce new substituents on the core structure, which is of key importance to optimize compound properties or introduce probes to further expand the possibilities of these compounds as tailored research tools to study G4 biology. Abstract : Stabilizing G4 DNA : In this study, synthetic methods to a new bis‐indole core structure with various substituents in different positions were developed. The compounds' interactions with G4 DNA were evaluated using an array of experimental and computational techniques revealing highly efficient G4 stabilizing compounds and information about key components for efficient G4 interactions.